Non-compliance with due motivation as cause of nullity of criminal sentences, superior court of Moquegua 2008 -2017 - Flores Arocutipa, Javier Pedro (2022)
Failure to comply with the due motivation influences the nullity of the judgments of first instance of the Criminal Chamber of the Superior Court of Justice between the years 2008-2017. The work is basic, descriptive, cross-sectional, bivariate. not experiential. 47 files have been collected where the judgment of first instance is nullified. Likewise, 21 magistrates, 10 prosecutors and 121 lawyers (2019) are interviewed. Information was collected in a research file and questionnaire. They were processed in Chi square and Spearman's correlation. In the application of the Chi square statistician, a Chi2 47.785 was found, which is greater than the Chi2 of the tables (26) with a sig. of 0.000, inferring that if the null variables are associated due to not applying the due written motivation. Of the 16 Spearman correlations generated between due motivation and competence, inference, means of proof, constitutional perspective, coherence, justification, they range from 16.8% to 39.5%. In absolute nullity, 72.4% were due to apparent motivation, 14.89% due to substantially inconsistent motivation and 14.89% due to Insufficient Motivation.